INTERNAL CONTROL SYSTEM AND SYSTEM ANALYSIS RISK MANAGEMENT ON COMPANY PERFORMANCE THROUGH GOOD CORPORATE GOVERNANCE ON PT REGIONAL DEVELOPMENT BANK EAST JAVA Tbk - Rendra Nur Suhartanta; Yuniningsih; Muhdajir Anwar (RADJA PUBLIKA, 2025)
This study aims to analyze the influence of Internal Control System and Risk Management System on Company Performance, with Good Corporate Governance as a mediating variable at PT Bank Pembangunan Daerah Jawa Timur Tbk. The specific objectives of this study are: (1) to analyze the influence of Internal Control System on Company Performance; (2) to analyze the influence of Risk Management System on Company Performance; (3) to analyze the role of Good Corporate Governance in mediating the influence of Internal Control System on Company Performance; and (4) to analyze the role of Good Corporate Governance in mediating the influence of Risk Management System on Company Performance. The population in this study is the Retail Credit Division, Credit Risk Analysis Division, Internal Audit Division, Risk Management Division, Compliance Division and Corporate Secretary of PT Bank Pembangunan Daerah Jawa Timur Tbk totaling 90 employees, using the Slovin formula obtained a sample of 73 respondents. The analysis method used is Partial Least Square (PLS) with the help of Smart PLS 3.0 software. The research results show that: (1) the Internal Control System can have a positive impact on Company Performance; (2) the Risk Management System also plays an important role in improving Company Performance; (3) Good Corporate Governance functions as a link that strengthens the influence of the Internal Control System on Company Performance; and (4) Good Corporate Governance also strengthens the relationship between the Risk Management System and Company Performance.